2017
DOI: 10.1186/s13584-016-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, hospital days and treatment costs of current and reduced sugar consumption in Israel

Abstract: BackgroundConsumption of sugar causes tooth decay, overweight and obesity related morbidities. This paper in response to the Minister of Health’s request, provides estimates of the mortality, morbidity and health care costs attributable to sugar consumption in Israel along with the effects of reducing sugar consumption.MethodsGender specific relative risks of many diseases from overweight (25 < =BMI < 30) and obesity (BMI > =30) were applied to the national gender specific prevalence rates of overweight and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…A major factor influencing claiming of benefits is awareness that such rights exist, and knowledge of the eligibility rules and claiming procedures [ 25 ]. A gap has been found between Jews and Arabs regarding knowledge and understanding of health insurance [ 26 ], and this may also be the case regarding NII benefit eligibility rights. In the case of conditions such as PPD, women in ethnic minority groups may also be less cognizant of the fact that they are suffering from a postpartum emotional disorder [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major factor influencing claiming of benefits is awareness that such rights exist, and knowledge of the eligibility rules and claiming procedures [ 25 ]. A gap has been found between Jews and Arabs regarding knowledge and understanding of health insurance [ 26 ], and this may also be the case regarding NII benefit eligibility rights. In the case of conditions such as PPD, women in ethnic minority groups may also be less cognizant of the fact that they are suffering from a postpartum emotional disorder [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may influence all ethnic groups, since tagging someone as mentally ill may interfere with future possibilities, such as employment. Further, most people experiencing mental health problems do not seek professional help, and the stigma of mental illness is considered a major barrier to seeking appropriate treatment [ 26 ]. A recent study conducted in Israel found that only 76% of women participated in a screening initiative for PPD and participation was associated with more positive attitudes toward seeking help [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the general hospital cost estimates as a base, estimates of disease‐specific out‐of‐hospital pharmaceuticals and other care (including ambulatory care) costs were made as follows: for breast cancer, CRC, and stroke, estimates were calculated directly from a recent similar study on the burden of sugar consumption in Israel; for dementia, depression, musculoskeletal disorders, chronic pancreatitis and COPD, estimates were based on overall health service costs . Therefore, hospital costs were multiplied by a factor of 13.3%/22.7% and (41.9% + 22.1%)/22.7% in order to estimate out‐of‐hospital pharmaceutical and other care costs.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, hospital costs were multiplied by a factor of 13.3%/22.7% and (41.9% + 22.1%)/22.7% in order to estimate out‐of‐hospital pharmaceutical and other care costs. Head and neck cancer cost estimates were based on the combined totals for all 8 cancers listed in the burden of sugar study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation